SYMPTOMS AND DIAGNOSIS OF HIRSCHSPRUNG’S DISEASE - Lassiyani Surya, Putu Ayu Ines; Dharmajaya, I Made (E-Jurnal Medika Udayana, 2014)
Hirschsprung disease is a disease that attacks the human digestive system, mainly in the large intestine (colon). In this disease, found enlargement of the colon (megacolon), due to the absence of ganglion cells in the distal intestine. Hirschsprung disease often affects neonates and even children, are often characterized by delays in spending the first meconium, bilious vomiting, abdominal distension. Methods diagnois do for Hirschsprung's disease was confirmed by biopsy, barium enema or contrast enema, and anorectal manometry. Early diagnosis is crucial to conduct rapid and appropriate treatment and to prevent complications.
Keywords: Hirschprung disease, symptoms, diagnose